Arctic National Wildlife Refuge (ANWR): Controversies for the 108th Congress - Corn, M. Lynne; Gelb, Bernard A.; Baldwin, Pamela (Library of Congress. Congressional Research Service., 2003)
This report discusses the ongoing debate about whether or not to approve energy development in the Arctic National Wildlife Refuge (ANWR). Current law forbids energy leasing in the Refuge. This report addresses several legislative options on the issue, as well as policymakers' arguments for and against development, especially in the wake of increasing terrorism since 2000-2001.